The Word Sponsor in the Investigation Report of Human Trafficking Cases: a Corpus-Based Meaning Study - Candraningsih, Made Dewi; Kurniawan, Eri; Supriadi, Rinaldi (Balai Bahasa Kalimantan Tengah, 2025)
This study aims to examine the denotative and connotative meanings of the word sponsor in the context of police investigation reports related to human trafficking cases in Indonesia, using a corpus linguistics approach supported by the AntConc software. The data consist of seven BAP documents from victims, witnesses, and suspects of TPPO cases, analyzed using the Word List, Concordance, and Collocates features to identify the frequency and collocational patterns of the word sponsor. The findings reveal that denotatively, sponsor refers to individuals or parties involved in the recruitment of prospective migrant workers. However, connotatively, the term carries a negative implication, often associated with illegal recruitment and exploitation practices embedded within human trafficking networks. Frequent collocates such as who recruited, on behalf of, and requested documents illustrate that sponsor is not semantically neutral, but socially constructed as a key actor in trafficking crimes. The findings indicate that changes in legal terminology are needed to improve accuracy and transparency in legal documents. As such, the results of this study can contribute to efforts to increase transparency and effectiveness of law enforcement in human trafficking cases.